Case report of brain death in a child due to COVID-19 and literature review - Tiantian Xu; Tian Liang; Jiamin Zhang; Yuqing Yan; Lianwei Lu; Lu Kuang; Changbing Wang; Misi Xiao; Yi Chen; Bing Zhu (BMC Infectious Diseases)
Abstract Purpose Although COVID-19 typically presents with respiratory symptoms, it can also lead to severe neurological manifestations in children. While case reports of COVID-19–associated encephalopathy (including acute necrotizing encephalopathy) have increasingly appeared, gaps remain regarding optimal management strategies and outcome predictors for children with rapid-onset neurological decline. This report aims to underscore the critical need for standardized clinical approaches to severe pediatric COVID-19–related encephalopathy. Methods In this case report, We detail the case of an 8-year-old girl who presented with fever, rash, headache, and recurrent seizures. Her diagnostic workup included polymerase chain reaction (PCR) testing for SARS-CoV-2 and a range of neurological assessments: contrast-enhanced computed tomography (CT) to evaluate structural changes, transcranial Doppler ultrasound to assess intracranial hemodynamics, and electroencephalography (EEG) to monitor electrical activity. Intensive therapeutic measures—encompassing mechanical ventilation, hemodynamic support, antimicrobial agents, and corticosteroids—were initiated. In addition, a targeted narrative literature review of pediatric COVID-19–associated neurological complications was conducted to contextualize this presentation. Results The patient tested positive for COVID-19;imaging revealed brain edem, and EEG suggested brain death. Despite aggressive critical care interventions, her condition did not improve, ultimately resulting in brain death. Our review of current literature revealed several reported instances of acute necrotizing encephalopathy in pediatric COVID-19, highlighting a growing body of evidence on the potential for severe central nervous system sequelae. Conclusion This case highlights the importance of early recognition and close neurological surveillance in pediatric patients with COVID-19. Although accumulating evidence describes COVID-19–related neurological complications such as acute necrotizing encephalopathy, uncertainties persist regarding definitive treatment protocols and long-term outcomes. Greater understanding of the underlying mechanisms and standardized management pathways is imperative to improve prognosis in this vulnerable population. Clinical trial Not applicable.